INTERFERENSI BAHASA SUNDA KE DALAM BAHASA INDONESIA PADA ANAK SEKOLAH DASAR KELAS 4-6 - Santi Wulandari; Vini Apriliani; Wikanengsih Wikanengsih (IKIP Siliwangi, 2018)
This research in the background by the use of two languages in communicating both oral and written. This, causing Sundanese language interference into Indonesian and Indonesian into Sundanese. The purpose of this research is to know and record the forms of language interference both Sundanese language into Indonesian and Indonesian into Sundanese students 4 - 6 students SDN Ciptamarga 2 dab grade 4 - 6 students of SDN Ciptamarga 3. This study uses descriptive method. Of all the utterances conveyed by the sample, the word is often used by students who use the Indonesian language that is (father, sepedah, karanjang). Meanwhile, the word is often used by students who use Sundanese language (uncle, male). From the results of data processing research, researchers found leksikal interference in Indonesian there are 75 and leksikal interference Sundanese there are 67.